MANAGEMENT OF EDUCATORS BASED ON Q.S LUQMAN Verse 13-19 - Putra Mahendra Gunawan Nasution (Sean Institute, 2022)
Educator management is one of the most important parts of education management. Educator management relates to individuals in the institutions/schools that run the system, especially education personnel such as teachers and staff employees who are directly on duty in the field with high demands, namely printing quality and quality output, so that they will continue to support programs that are proclaimed by schools to improve the quality of educational services. To realize quality teacher resources is inseparable from the role of the principal in managing the available education personnel in schools. In this case, increasing productivity and work performance can be done by improving management in the workplace through the application of modern educator management concepts and techniques. Assessment of education personnel is focused on individual achievements and their participation in school activities. An educator must have a good managerial system in order to create quality and qualified educators so that they can print quality outputs. Teachers who have a good managerial system are easier to run the existing system in schools, so that the school's vision and mission can be realized. Teachers must pay attention to things that can support success in learning before learning takes place. Sufficient funds, adequate facilities will not be enough if the educators do not have a good managerial system, because teachers have a very important role to support the achievement of a goal in school.